Ideea de calitate a vieții în principiul psihodramei - Beca, Elena (Calitatea Vieții, 1992)
The principle of psychodrama developed by J.L.Moreno originates on Kierkegaard’s existentialism, since it is based on the individual’s use of imagination to reevaluate his/her own situation in a given context. The evaluating process within psychodrama is similar to that of the subjective evaluation as the very essence of the quality of life.